Analisis Penerapan Sistem Informasi Akuntansi Berbasis Website dalam Pengelolaan Keuangan pada Perusahaan Manufaktur - Nur Azizah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the implementation of a web-based Accounting Information System (AIS) in financial management at a manufacturing company, with a case study at PT Hamifaro Jaya Lestari. The background of this research is based on the company’s initial condition which still relied on manual bookkeeping and spreadsheet assistance, resulting in several problems such as recording errors, data duplication, delays in financial reporting, limited access to financial information, and weak internal control. These conditions affected the effectiveness of cash flow monitoring and managerial decision-making processes.The research employed a qualitative method with a case study approach. Data collection techniques included in-depth interviews, direct observation of business processes, and documentation of financial records to obtain comprehensive and contextual data regarding conditions before and after system implementation. The analysis focused on cash receipt processes, cash disbursement procedures, financial report preparation, and internal control evaluation based on the COSO framework, which includes the control environment, risk assessment, control activities, information and communication, and monitoring.The results indicate that the implementation of a web-based AIS improves the accuracy and consistency of transaction recording, accelerates automated financial reporting, provides real-time financial information, and enhances transparency and accountability of financial data. In addition, the system increases operational efficiency through data integration across departments, reduces dependence on manual processes, and strengthens internal control through user access restrictions and audit trail features. Functional testing shows that the cash receipt, cash disbursement, reporting, and user management modules operate according to business needs. Therefore, a web-based AIS is considered an effective and feasible solution for improving financial management quality and supporting faster and more accurate managerial decision making